2013
DOI: 10.1371/journal.pntd.0002263
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis-derived Cry5B Has Potent Anthelmintic Activity against Ascaris suum

Abstract: Ascaris suum and Ascaris lumbricoides are two closely related geo-helminth parasites that ubiquitously infect pigs and humans, respectively. Ascaris suum infection in pigs is considered a good model for A. lumbricoides infection in humans because of a similar biology and tissue migration to the intestines. Ascaris lumbricoides infections in children are associated with malnutrition, growth and cognitive stunting, immune defects, and, in extreme cases, life-threatening blockage of the digestive tract and aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 46 publications
3
54
0
Order By: Relevance
“…A recent study reported a dose-dependent toxicity of CGL2, CCL2, AAL, and MOA toward larval and adult stages of the barbers pole worm, Haemonchus contortus in vitro, in which toxicity of the lectins correlated with their binding to the intestinal epithelium of this animal-parasite nematode (Heim et al 2015). Successful in vivo applications of nematotoxic, carbohydrate-binding protein toxins of microbial origin against parasitic nematodes were demonstrated for the Bacillus thuringiensis toxin Cry5B against the hookworm Ancylostoma ceylanicum in hamsters and against the large roundworm Ascaris suum in pigs (Cappello et al 2006;Hu et al 2012;Urban et al 2013). The nematotoxicity of all those carbohydrate-binding proteins proven to be effective against parasitic nematodes had previously been demonstrated in C. elegans, showing the power of this model organism for detection and characterization of nematotoxic proteins.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…A recent study reported a dose-dependent toxicity of CGL2, CCL2, AAL, and MOA toward larval and adult stages of the barbers pole worm, Haemonchus contortus in vitro, in which toxicity of the lectins correlated with their binding to the intestinal epithelium of this animal-parasite nematode (Heim et al 2015). Successful in vivo applications of nematotoxic, carbohydrate-binding protein toxins of microbial origin against parasitic nematodes were demonstrated for the Bacillus thuringiensis toxin Cry5B against the hookworm Ancylostoma ceylanicum in hamsters and against the large roundworm Ascaris suum in pigs (Cappello et al 2006;Hu et al 2012;Urban et al 2013). The nematotoxicity of all those carbohydrate-binding proteins proven to be effective against parasitic nematodes had previously been demonstrated in C. elegans, showing the power of this model organism for detection and characterization of nematotoxic proteins.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…1,2 Current treatment revolves around mass drug administration (MDA) with benzimidazole anthelmintics (primarily albendazole), but widespread anthelmintic resistance in veterinary husbandry and reports of low efficacy of albendazole in human therapy suggest that new anthelmintics are urgently needed. 3,4 One of the more promising new anthelmintics in development for STHs is the crystal (Cry) protein Cry5B, derived from Bacillus thuringiensis , 5 which has been shown to be highly effective against in vivo infections of STHs such as Ascaris 6 and hookworm. 7 Cry5B is a member of the three-domain B. thuringiensis Cry proteins, which are pore-forming proteins that target the invertebrate (insect/nematode) intestine, in the case of Cry5B by binding to invertebrate-specific glycolipids present on the apical surface of the nematode intestine.…”
mentioning
confidence: 99%
“…The preparation of infective A. suum eggs and inoculation of two pigs from the Beltsville Swine Herd were completed as described previously (Urban et al., 2013). Seven days after inoculation with 15,000 infective eggs, the lungs were removed and mixed with an equal volume of 37 °C normal saline in a Waring blender container with rotating cutting blades, and homogenized for approximately 20 s to produce a tissue suspension of fragments of ∼0.5 cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Seven days after inoculation with 15,000 infective eggs, the lungs were removed and mixed with an equal volume of 37 °C normal saline in a Waring blender container with rotating cutting blades, and homogenized for approximately 20 s to produce a tissue suspension of fragments of ∼0.5 cm 3 . Host-stage L3s were isolated from the lung tissue using an agar-gel method (Urban et al., 2013), transferred to RPMI-c and kept in a 37 °C, 5% CO 2 , incubator until use. For EPG recordings, 10% (v/v) calf serum (CaS; Lonza BioWhittaker 14-401F, Walkersville, MD, USA) was added to RPMI-c.…”
Section: Methodsmentioning
confidence: 99%